ACCIDENT RISK COVERAGE SYSTEM FOR RENTAL CARS IN THE PERSPECTIVE OF IJARAH 'ALA AL-MANFA'AH CONTRACT - Alia Ramadhani (JURISTA: Jurnal Hukum dan Keadilan, 2021)
Risk coverage in car rental practices is the company's responsibility to the consumer if something untoward happens. The responsibility given by Zahri Rental is in the form of compensation. The purpose of this study is to find out how the form of coverage for the risk of accidents between the renter and the rental owner, how the consequences of the risks borne by the rental car and how the perspective of the ijarah 'ala al-manfa'ah contract on the accident risk coverage system by the rental car. In this research, the author uses qualitative research methods and uses an empirical normative approach. The results show that the form of accident risk coverage between the lessee and the lessor is regulated according to the type of accident that occurs. In the case of damage to the rental object that is not due to the intention of the renter, Zahri Rental imposes full responsibility on the renter and the renter is required to pay more rent when the rental object enters the insurance workshop, even though the renter has initially paid an insurance claim if an accident occurs one day. This is because Zahri Rental considers that the consequences to be borne are very high if the car is not operational when it enters the insurance workshop, which causes Zahri Rental to lose income. Therefore, the risk coverage system applied is not in line with the perspective of the Ijarah 'ala al-manfa'ah contract.